A study on solar disinfection of drinking water using flat-plate solar collector - Donasco, Edgar Alan A. (2000)
Lack of access to a reliable steady supply of safe drinking water remains a problem for developing countries like the Philippines. A treatment method that is simple, low-cost, effective, and sustainable needs to be in place as an alternative.
Solar disinfection process for drinking water is a method that is applicable in a household or institutional level. The technology is simple, reliable, and operationally cheap as it requires only energy from the sun to run it. Synergetic action of both heat and radiation (UV-A) from the sun is potent in inactivating and destroying pathogenic microorganisms present in water.
This study assessed the local suitability of the solar disinfection process through developing and testing a fabricated Solar Disinfection (SODIS) Plant. The set up consisted of the raw and treated water tanks, solar reactor which is basically a flat-plate solar collector for combined heating and irradiation, and piping accessories. Tests for thermal and microbiological performance proved that solar disinfection through the SODIS Plant is a viable option for water disinfection. Several trials showed that setting the water temperature to at least 50 ̊C resulted to complete inactivation of Total coliform microorganisms. On average day, with a solar intensity of 0.58 kW/m², the SODIS Plant is able to raise the water temperature to its minimum effective setting of 50 ̊C within 2 hours.Operating at 22% net thermal efficiency, the plant is able to generate 40 liters/day per m² of reactor area.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Drinking water -- Purification -- Disinfection; Solar collectors